Models and Techniques in Stroke Biology - Tripathi A.K.; Singh A.K. (My University, 2025)
This book summarizes various tools and techniques used to provide insights into the cellular and molecular pathophysiology of stroke. It also presents rodent animal models to help shed light on the pathophysiology of ischemic stroke. Presenting the latest information on the different types of stroke, including embolic, filament, photothrombotic, and bilateral common carotid artery, the book also describes techniques that are used for confirmation of stroke surgery, such as laser speckle imaging (LSI) and laser Doppler flowmetry (LDF), and discusses the non-human primates that are used in stroke surgery, cerebral venous sinuous thrombosis, and neurobehavioral assessment. Lastly, it analyzes various neuroprotective agents to treat and prevent ischemic stroke, and examines the challenges and advances in treating and preventing acute ischemic stroke. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2021.